Correlates of Health Care Workers' Knowledge and HIV-Exposed Infant Immunization Counseling Practice in Northern Nigeria - Fatimah Hassan-Hanga; Zubairu Iliyasu; Sadiq Ajuji; Musa M. Bello; Safiyya Abdulkadir; Nafisa Nass; Hamisu M. Salihu; Muktar H. Aliyu (Global Health and Education Projects, Inc., 2020)
Background: Human Immunodeficiency Virus (HIV)-exposed and HIV-infected infants are at increased risk of vaccine-preventable diseases. However, little is known about health care workers' knowledge and immunization counseling practices in this population. We determined the predictors of health care workers' knowledge of vertical transmission risks, HIV exposed/infected infant immunization, and counseling practices in a tertiary center in Northern Nigeria. Methods: A cross-section of 297 health workers were interviewed using a structured, validated questionnaire. Knowledge and HIV-exposed infant immunization counseling practices were analyzed, and adjusted odds ratios for predictors were derived from logistic regression models. Results: Of the 297 participating health care workers, (32.3%, n=96) had adequate knowledge of HIVexposed/infected infant immunization. Two-thirds (67%, n=199) of the participants appropriately identified the timing of infant diagnosis, while (73%, n=217) and (56.2%, n=167) correctly categorized infants as HIV-exposed and HIV-infected, respectively. Only (19.5%, n=58) participants had ever counselled a HIVpositive mother on infant immunization. Knowledge was predicted by work unit (HIV clinic vs. Obstetrics & Gynecology clinic), (Adjusted Odds Ratio (AOR) =3.78, 95% CI: 1.27-5.54), age (30-39 vs. <30 years), (AOR=2.24, 95% CI:1.19-5.67), years of experience (≥10 vs. <5), (AOR=1.76, 95% CI: 1.15-6.04), number of children (1 vs. 0), (AOR=1.73, 95% CI:1.14-4.23), infant immunization training (yes vs. no), (AOR=1.57, 95% CI:1.12-5.43), female sex (AOR = 1.17, 95% CI:1.06-2.21), profession (nurse/midwife vs. physician), (AOR=0.44, 95% CI:0.21-0.94) and previous HIV test (no vs. yes), (AOR=0.67, 95% CI:0.21-0.83). Conclusion and Global Health Implications: Knowledge of HIV-exposed infant immunization was low and counseling practices were sub-optimal. Both immunization knowledge and counseling practices were predicted by demographic, professional, and training variables. Our findings indicate the need for educating health care workers on HIV exposed/infected infant immunization policy and improving counseling skills through capacity-building programs. Copyright © 2021 Iliyasu et al. Published by Global Health and Education Projects, Inc. This is an open-access article distributed under the terms of the Creative Commons Attribution License (CC BY 4.0) which permits unrestricted use, distribution, and reproduction in any medium, provided the original work, first published in this journal, is properly cited.